Enhancing integration of offsite construction and building information modelling : study of challenges, strategies, and stakeholders in New Zealand construction industry : a thesis submitted in fulfilment of the requirements for the degree of doctor of Philosophy in Building and Construction, School of Built Environment, College of Science, Massey University, New Zealand - Kordestani, Nazanin (Massey University, 2025)
The development of prefabrication has progressively evolved into more advanced and comprehensive full-scale offsite manufacturing (OSM) processes within the construction industry, suggesting a continuum where prefabrication represents an initial stage and OSM signifies a more integrated and mature stage of industrialised construction practices. Offsite construction (OSC), which involves manufacturing components in controlled environments, has gained popularity for its efficiency and waste reduction benefits. Despite these advantages, the transition to OSC also presents various challenges. Advanced technologies such as Building Information Modelling (BIM) have been suggested as practical tools for mitigating these challenges, facilitating digital construction models, and enhancing the delivery process through a collaborative environment. The adoption of OSC and BIM is complex, particularly when considering their individual implementation as well as their integration. While each approach presents its own set of challenges, the combined adoption and integration of OSC and BIM introduce additional layers of complexity, requiring alignment across technical, organisational, and strategic dimensions. A structured guideline could assist project stakeholders and organisations in navigating these challenges throughout the project lifecycle. Integration is influenced by the external environment at the project, organisation, and industry levels, and these challenges vary at different points during the project life cycle. Therefore, it is essential to fully map these challenges at different levels and stages to devise and deploy appropriate strategies. Currently, a multi-level integration framework is needed to focus on these challenges and reduce them through strategies involving relevant stakeholders. This study addresses this gap by developing an integration framework with a specific focus on integration challenges and understanding the relationships between challenges and strategies. The study commenced with a scientometric analysis, a systematic literature review, and semi-structured expert interviews to investigate OSC and BIM integration challenges. Multiple themes were explored, and the triangulation of these methods supports the creation of applicable knowledge in this field. The scientometric analysis identified multiple gaps, research trends, and pioneer countries within the scope of the research. The identification of pioneer countries provided insights into global leadership, best practices, and enabling factors for successful OSC and BIM integration. These countries serve as benchmarks, offering transferable lessons and contextual understanding that informed the study’s aim of addressing integration challenges and developing a strategic framework applicable to the New Zealand construction industry. The findings revealed a classified cluster of 35 challenges for OSC and BIM implementation and 21 integration strategies. The interviews provided comprehensive and complementary data sets and analyses, and the findings from the systematic literature review and interviews structured the integration framework. Following this, a survey questionnaire was administered to measure the identified challenges and explore strategies through various methods, including Factor Analysis, resulting in eight groups of significant underlying factors affecting OSC and BIM integration. Recommendations to enhance integration were provided, identifying underlying variables such as implementation costs, integrated knowledge deficit, competency and preparedness deficit, integration facilitators, external support and policy regulation, BIM-driven OSC readiness, BIM-enabled collaboration and facilitation, and BIM-enabled OSC enhancement. This step was followed by Structural Equation Modelling (SEM), which employed three different path analysis models for integration variables, clarifying that not all variables have similar impacts on integration; some exhibit significant positive or negative effects, while others are not significant at all. A questionnaire survey was then utilised to examine the challenges specific to various organisational levels and project lifecycle phases. Four independent case studies were used to develop and validate the survey findings, demonstrating the five levels of OSC and BIM integration maturity in the construction industry: initiate, managed, defined, quantitatively managed, and optimized. The findings demonstrated that the same set of challenges could occur during multiple project phases as well as at different organisational levels. Furthermore, each maturity level has characteristics that influence the strategies applied. The findings highlight that challenges vary across the project lifecycle and different maturity levels. Nevertheless, continuous collaboration among stakeholders is essential to mitigate these challenges. From lower to higher levels of OSC and BIM integration maturity, the nature of challenges evolves from basic understanding and knowledge acquisition to the development of standards and guidelines. This framework aims to enhance the integration process by identifying challenges related to maturity levels and the project lifecycle, ultimately increasing the efficiency and effectiveness of OSC and BIM integration practice. By offering a comprehensive framework to address these challenges, the outcome of this research equips project stakeholders with a robust tool to navigate complexities and maximise the benefits of integration throughout the project lifecycle. Moreover, the emphasize on stakeholder collaboration highlights the importance of collective efforts in overcoming integration hurdles, ultimately contributing to the advancement and success of construction projects. The aim of the framework is to enhance the integration process by identifying challenges related to maturity levels and the project lifecycle, ultimately increasing the efficiency and effectiveness of OSC and BIM integration practice. This integration focuses on aligning OSC methodologies with BIM’s information management capabilities, ensuring optimized workflows, improved collaboration, and streamlined project delivery processes. The study's findings are crucial for understanding and strategically addressing challenges, improving collaboration, and advancing OSC and BIM integration in the construction industry. The study narrowed the gap in understanding the challenges and strategies and empirically explored critical factors to improve integration. Findings confirmed that implementing effective management could potentially help reduce integration challenges
Figure 9.2 (=Harlos et al., 2022 Fig 2) is © 2025 Water New Zealand and was removed.
Keywords: Offsite Construction (OSC), Building Information Modeling (BIM), integration, challenges, strategies, stakeholders; 330204 Building information modelling and management